Sam and Kevin both worked hard over the summer. Together they earned a total of $425. Kevin earned $ 25 more than Sam.
a) Write a system of equations for the situation. Use s for the amount Same earned and k for the amount Kevin earned.
b) Graph the equations in the system.
c) Use your graph to estimate how much each person earned.


Solve the system of equations by substitution.
6= -4x + Y
-5x - Y =21

Solve the system by the elimination method.
2x + y=20
6x - 5y=12

Please help I do not understand how to do this ..Thanks

Respuesta :

QUESTION 1


a)


Let


[tex]s [/tex]


represent the amount Same earned and


[tex]k[/tex]


represent the amount Kevin earned.




We were told that, they earned $425 dollars together.




This implies that,



[tex]k+s= 425---eqn(1)[/tex]




It was also given that, Kevin earned $25 more than Same.




This implies,



[tex]k-s=25---eqn(2)[/tex]




For equation (1), when


[tex]s=0[/tex]



[tex]k=425[/tex]


We plot the point,




[tex](425,0)[/tex]


When


[tex]k=0[/tex]


[tex]s=425[/tex]




We plot the point,


[tex](0,425)[/tex]



Similarly for the second equation when


[tex]s=0[/tex]



[tex]k=25[/tex]



This gives the point,


[tex](25,0)[/tex]



When


[tex]k=0[/tex]


[tex]s=-25[/tex]



We plot


[tex](0,-25)[/tex]


and draw a straight line through them.




We can see from the graph that the two points intersect at  


[tex](225,200)[/tex]



This implies that


[tex]k=225\:and\:s=200[/tex]



Therefore Kevin earned $ 225

and Same earned $ 200




QUESTION 2



The given system is



[tex]6=-4x + y---eqn(1)[/tex]



and



[tex]-5x-y=21---eqn(2)[/tex]




From equation (2),



[tex]y=-5x-21---eqn(3)[/tex]



Put equation (3) into equation (1).





This implies that,



[tex]6=-4x-5x-21[/tex]



Group like terms,



[tex]6+21=-4x-5x[/tex]



Simplify, to get,



[tex]27=-9x[/tex]



[tex]x=-3[/tex]




We substitute this value into equation (3) to get,




[tex]y=-5(-3)-21[/tex]




[tex]y=15-21[/tex]



[tex]y=-6[/tex]


Therefore the solution is


[tex](-3,-6)[/tex]




QUESTION 3




We want to solve,



[tex]2x+y=20---(1)[/tex]



and



[tex]6x -5y=12---(2)[/tex]





We multiply equation (1) by 3 to get,



[tex]6x+3y=60---(3)[/tex]




Equation (3) minus equation (2) will give us,



[tex]8y=48[/tex]



This means


[tex]y=6[/tex]



Put this value into equation (1) to get,




[tex]2x+6=20[/tex]



[tex]2x=20-6[/tex]


[tex]2x=14[/tex]



[tex]x=7[/tex]


The solution is


[tex](7,6)[/tex]




Ver imagen kudzordzifrancis

Answer:

Sam earns $200 and Kevin earns $225.

x , y= -3 , -6 by substitution

x , y= 7, 6 by elimination

Step-by-step explanation:

a) Let the amount earned by Sam = s and the amount earned by Kevin = k

We are given, that they both earn total $425 i.e. s + k = 425

Also, Kevin earns $25 more than Sam i.e. k = s + 25

Hence, the system of equations comes out to be:

s + k = 425

-s + k = 25

b) Take s = x and k = y. See the graph plotted below

c) As the intersection point from the graph comes out to be (s,k) = (200,225)

Therefore, Sam earns $200 and Kevin earns $225.


Now, we have the system

-4x + y = 6

-5x - y = 21

We need to use substitution method.

Take y= -5x - 21 from the 2nd equation and put it in the 1st.

We get, -4x - 5x - 21 = 6  i.e.  -9x = 27  i.e.  x= -3

Now, substitute this value of x in any of the equation to find y.

We get, -5*(-3) - y = 21  i.e.  y = 15 - 21  i.e.  y = -6


Now, we are given the system,

2x + y = 20

6x - 5y = 12

We need to use elimination method.

Multiply 5 by equation 1. We get,

10x + 5y = 100

6x - 5y = 12

Adding the above equations, we get, 16x = 112  i.e. x = 7

Put this value in any of the equation to find the value of y.

We get, y = 20 - 2x  i.e.  y = 20 - 2*7  i.e.  y = 20 - 14  i.e. y = 6

Ver imagen SerenaBochenek